OCCUPATIONAL STRESS AND ASSOCIATED FACTORS AMONG HOSPITAL NURSES (Tạp chí Y học Cộng đồng, 2026)
Background: Nursing is a profession with high physical and psychological demands, making nurses vulnerable to occupational stress, which may affect both their health and the quality of patient care.Objective: To assess the level of occupational stress and identify associated factors among nurses at several hospitals in Can Tho City, Vietnam.Methods: A cross-sectional descriptive study was conducted on 267 nurses using an electronic questionnaire (Google Forms) from July to August 2025. Statistical analyses included descriptive statistics (frequencies, means, and standard deviations) and logistic regression to identify associated factors.Results: The 12-item stress scale demonstrated excellent internal consistency (Cronbach’s Alpha = 0.96). The mean stress score was 41.8 ± 15.0. The highest stressors were “occupational health problems” (3.85 ± 1.57), “lack of time for family” (3.72 ± 1.46), and “work-related fatigue” (3.70 ± 1.59). Stress levels were classified as mild in 37.4% of nurses, moderate in 37.1%, severe in 23.2%, and absent in only 2.3%. Significant demographic factors associated with stress included self-reported health status, having children, and being a single parent (p < 0.05). Significant work-related factors were the working department and daily working hours (p < 0.05).Conclusion: Most nurses experienced moderate to high levels of occupational stress, particularly related to workload, insufficient family time, and occupational health issues. Interventions at both organizational and individual levels are needed to support nurses’ physical and mental health and to improve the working environment.
Keywords: occupational stress, nurses, hospital.